Factors Influencing the Quality of Life of Korean Elderly Women by Economic Status - Kwon, Myoungjin (Int J Environ Res Public Health, 2020)
Purpose: This study aimed to determine whether there are differences in the factors affecting the quality of life (QOL) of elderly women in South Korea according to their perceived economic status. Methods: Data were extracted from the Seventh Korea National Health and Nutrition Examination Survey conducted in 2016. The participants were 879 women over the age of 65 years, who were divided into three groups: high, medium, and low based on their perceived economic status. The study variables were classified into three categories: general characteristics, physical factors, and psychological factors. General characteristics included age, education level, employment, activity restriction, frequency of breakfast/week, frequency of lunch/week, and frequency of dinner/week. Physical factors included disease status, weight change, consumption of alcohol, number of days of walking per week, duration of walking at a time, body mass index (BMI), and discomfort due to changes in hearing. Psychological factors included stress, subjective body awareness, subjective health status, depressive symptoms, and QOL. Complex sample crosstabs and chi-square tests were conducted, and regression was performed to examine the association between the variables by economic status. Results: The factors that influenced the QOL of elderly women with low economic status were arthritis, alcohol consumption, subjective health status, and depressive symptoms, with an explanatory power of 54.3% (F = 14.94, p < 0.001). The factors that influenced the QOL of the medium economic status group were activity restriction, frequency of dinner/week, arthritis, number of days of walking per week, BMI, stress, subjective health status, and depressive symptoms, with an explanatory power of 48.6% (F = 9.82, p < 0.001). For the high economic status group, influential factors were age, restricted activity, arthritis, number of days of walking per week, stress, and depressive symptoms with an explanatory power of 49.0% (F = 69.76, p < 0.001). Conclusions: This study identified different factors that contributed to the QOL of elderly women by economic status.